2017
DOI: 10.1017/s2045796017000129
|View full text |Cite
|
Sign up to set email alerts
|

In-patient suicide in psychiatry – an Indian experience

Abstract: Epidemiology and Psychiatric Sciences (2017), 26, 565-569.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…17 The use of suicide risk assessments is now been recommended for all inpatients by the TJC. 12 Furthermore, regular training staff from all disciplines, and encouraged to keep informed with newer evidence related to patient's suicide risk. The poster campaigns and mandatory lectures and training have proven beneficial in identifying and responding to high-risk patients.…”
Section: Improving Detection and Awarenessmentioning
confidence: 99%
See 4 more Smart Citations
“…17 The use of suicide risk assessments is now been recommended for all inpatients by the TJC. 12 Furthermore, regular training staff from all disciplines, and encouraged to keep informed with newer evidence related to patient's suicide risk. The poster campaigns and mandatory lectures and training have proven beneficial in identifying and responding to high-risk patients.…”
Section: Improving Detection and Awarenessmentioning
confidence: 99%
“…The first week of inpatient care is considered critical, and as much as 77% of deaths by suicide have been reported during this phase. 8,[11][12][13] A systematic review suggested a higher probability of death by suicide in inpatients with schizophrenia when on leave compared with patients with affective disorder. Furthermore, since agreed leaves were usually given later on during the admission, patients with affective disorders have a greater risk earlier in the hospitalization.…”
Section: Identifying Individuals At Riskmentioning
confidence: 99%
See 3 more Smart Citations